ANALISIS PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus pada Warung Spesial Bebek Goreng Andalan) - Hidayat, Rizki Sappitu; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2016)
The food industry lately become a reference glimpsed by employers because its potential is quite large. Food entrepreneurs are always competing to build the public perception. Many companies implement specific strategies to influence consumer purchasing decisions. These activities aim to influence consumer purchase decisions so as to achieve the maximum profit in the sale.The population in this study were all employees of Special Warung Bebek Goreng mainstay Semarang. In this study, the study population refers to consumers who never make purchases at the point Deals Fried Duck mainstay Semarang unknown number. In consideration of the population is too much, this research is based on sampling.The result of this study showed that perception of price variable has positive and significant effect on employee purchasing decisions and promotion variable has positive and significant effect on employee purchasing decisions. Good price and good promotion will be able to improve purchasing decisions.